Study of the History of the Birth of Pesantren in Madura: Perdikan Reform to Pesantren - Ach. Syafiq Fahmi; Faiqatul Munawwarah; Maimun, Maimun; Intan Dwi Permatasari (Penerbit Hellow Pustaka, 2024)
Pesantren as a traditional Islamic educational institution in Madura has an important role in shaping the character of the local community. The focus of this study is to examine in depth the history of the birth of pesantren in Madura and its relationship to the reformation from perdikan to pesantren. By using the library study method, this study is expected to explore the transformation of pesantren in Madura as a response to social change. The results of the study indicate that the Islamization Process in Madura can be said to be an effort to preach that began between the 7th century and the 15th century, basically questions such as when, who, and how the beginning of pesantren in Madura are not easy to answer. However, in general, there are two paths that can be seen in the process of Islamization and the beginning of pesantren in Madura, namely the royal path and the path of the da'i or sunan. The role of perdikan in the development of pesantren in the early days was to free land used for religion, holy places, and services provided by the king. The function of this pesantren is exempt from state taxes. Because the land used is for religious interests as well as having the right to regulate its regional autonomy. Perdikan land has a significant influence on the development of Islamic boarding schools in Madura. By utilizing land optimally, Islamic boarding schools can not only improve the quality of education provided, but also contribute to strengthening the community and economic independence of the surrounding community.